Insights in managing refractive surprise after cataract surgery: A case series - Oktaliani, Rahayu; Budiman; Knoch, Andrew Maximilian Herman; Sugiarti, Emmy Dwi; Tjokrovonco, Ludwig Melino (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Improvements in cataract surgery techniques and intraocular lens (IOL) calculations have raised patient expectations for precise visual outcomes. Refractive surprise occurs when the post-operative refractive outcome differs from the intended target, leading to unexpected visual outcomes. Secondary piggyback IOL implantation and IOL exchange are techniques to correct the refractive surprise. We presented some case series of refractive surprise after cataract surgery. Case I was A 55-year-old woman presented with the complaint of blurred vision in her left eye after cataract surgery ten months before. The visual acuity was 0.125 in the right eye (RE) and 0.05 in the left eye (LE). The best-corrected visual acuity of the left eye was 0.63 with a refraction of S+6.00 C-0.50 × 20°. She was diagnosed with hyperopic surprise in the left eye and pseudophakia in both eyes. The piggyback intraocular lens implantation procedure was chosen to correct the refractive surprise. Case II was A 72-year-old man presented with the complaint of blurred vision in his right eye after cataract surgery five years before. The visual acuity was 1/60 in his right eye and 0.16 in his left eye. The best-corrected visual acuity of the right eye was 0.4 with a refraction of S-14.00 C-1.50 × 125°. He was diagnosed with myopic surprise in his RE. The IOL exchange to scleral fixation with the Yamane technique implantation procedure was chosen to correct the refractive surprise. Piggyback IOL implantation and IOL exchange are proven, safe, and effective methods for correcting refractive surprises following cataract surgery.